G234(P) Case report: premature adrenarche and pseudohypoparathyroidism – mechanistically linked or coincidence?. (12th March 2018) - Odone, JC; Kumar, Y; Burren, CP
Abstract : Aims: To describe a case of premature adrenarche with pseudohypoparathyroidism, an as yet unreported combination. Methods: An otherwise well 8 year old girl presented to a Paediatric Endocrine Clinic with early pubic hair development suggestive of premature adrenarche. Blood tests revealed hypocalcaemia, elevated phosphate and highly elevated parathyroid hormone (PTH) level, giving a biochemical diagnosis of pseudohypoparathyroidism. She had normal stature (height 50th – 75th centile) and no phenotypic features of Albright Hereditary Osteodystrophy (AHO) were identified: obesity, learning difficulties, brachydactyly, short stature, shortened 4th/5th metacarpals, dental hypoplasia or a rounded face. Results: Blood tests revealed low corrected calcium 1.49 mmol/L (reference range 2.2–5.7), elevated phosphate 2.78 mmol/L (reference range 0.9–1.8) and serum PTH level almost 10 times the upper limit of normal at 66.4 pmol/L (reference range 1.6–6.9), with normal Vitamin D 94 nmol/L, normal thyroid function: Free T4 5.4 pmol/L (reference range 12–22); TSH 4.8 miu/L (reference range 0.27–4.2). Hand and wrist Xray for bone age assessment revealed mildly shortened 4th/5th metacarpals, a phenotypic feature of AHO. Genetic testing results and MRI head to screen for white matter calcification are awaited. These will help clarify which subtype of pseudohypoparathyroidism is responsible for this presentation. Management: She commenced oral calcium carbonate and alfacalcidol to correct the severe calcium deficiency and to normalise PTH levels. Progressively increasing doses have been required. Conclusion: Pseudohypoparathyroidism is a rare endocrine disorder characterised by resistance to the action of PTH. It has been classified within the AHO group. Recognition of a broader range of phenotypic features and underlying mutations has led to a novel classification system of iPPSD (inactivating PTH/PTHrP signalling disorders) developed by the EuroPHP network. GNAS1 mutations have been identified underlying various pseudohypoparathyroidism subtypes, resulting in reduced function of the G-protein coupled to the PTH receptor. G-proteins are also coupled to other hormone receptors; patients with AHO or iPPSD often present with a range of endocrine disorders, for example hypothyroidism. There are cases of individuals with GNAS1 mutations presenting concurrently with precocious puberty and pseudohypoparathyroidism but no reported case of premature adrenarche and pseudohypoparathyroidism. Awaited genetic studies in our case may be informative.